WEED MANAGEMENT IN CHIA (Salvia hispanica L.) THROUGH HERBICIDE APPLICATIONS UNDER SEMI-ARID CONDITIONS OF INDIA (Applied Biological Research, 2025)
A field experiment was conducted under arid conditions of western Rajasthan (India) to evaluate the efficacy of pre- and post-emergence herbicides for weed management in chia (Salvia hispanica L.). The study employed a randomized block design with ten treatments, comprising two doses each of bentazon (500 and 750 g ha⁻¹), fluazifop-p-butyl (100 and 200 g ha⁻¹), sulfentrazone (50 and 75 g ha⁻¹), and pendimethalin (200 and 400 g ha⁻¹), along with a weed-free control and a weedy check.Key weed control indices, viz., weed control index (WCI), weed persistence index (WPI), crop resistance index (CRI), and herbicide efficiency index (HEI), were assessed along with crop growth and yield parameters.The results revealed that sulfentrazone and pendimethalin, applied as pre-emergence herbicides, provided superior early-season weed control with WCI values of 85.4% and 82.7% at 30 days after sowing (DAS), respectively. Among post-emergence treatments, bentazon gave the highest WCI (83.2%) at harvest and demonstrated superior CRI (9.33) and HEI (2.45), indicating strong crop safety and herbicide effectiveness.The highest seed yield (554 kg ha⁻¹) was obtained in the weed-free treatment, followed by bentazon @ 750 g ha⁻¹ (495 kg ha⁻¹) and sulfentrazone @ 75 g ha⁻¹ (467 kg ha⁻¹), showing respective yield increases of 90.4% and 60.5% over the weedy check.The study suggested that an integrated weed management approach, combining pre-emergence herbicides (sulfentrazone or pendimethalin) with post-emergence bentazon, can significantly improve weed control and productivity in chia under arid farming systems.
Keywords: Arid agriculture; bentazon; chia; crop resistance index; herbicide efficacy; sulfentrazone; weed control index